Teachers' professional identity and job burnout: The mediating roles of work engagement and psychological capital - Zhang, Qinhan; Li, Weijian; Gao, Jianwei; Sun, Binghai; Lin, Shuwei (Psychology in the schools, 2024)
Teacher burnout refers to teachers’ inability to cope with work stress smoothly. Previous studies have revealed that job burnout is negatively related to professional identity; however, little is known about the mechanism underlying the relationship between teacher professional identity and job burnout. This study tested the mediating effects of work engagement and psychological capital in the relationship between professional identity and job burnout. A descriptive correlational design was employed. Measures included the Professional Identity Scale, Utrecht Work Engagement Scale, Psychological Capital Questionnaire, and Professional Quality of Life Scale. A total of 3147 primary and secondary school teachers in China, of which 2220 were women (70.5%) and 927 were men (29.5%), with an average age of 39 years (SD = 8.74), completed the questionnaire survey. SPSS PROCESS macro (version 21) was used to explore the mediating roles of work engagement and psychological capital in the relationship between professional identity and job burnout. Professional identity, work engagement, and psychological capital significantly negatively affected job burnout. Work engagement and psychological capital, when occurring in parallel or sequentially, partially mediated the relationship between professional identity and job burnout. Job burnout among teachers with high professional identity can be eliminated by increasing work involvement and promoting exercise to improve their psychological capital. These findings provide implications for preventing burnout among teachers in the future. Job burnout among teachers with high professional identity can be eliminated by increasing work involvement and promoting exercise to improve their psychological capital. These findings provided implications for preventing burnout among teachers on the future. PRACTITIONER POINTS The relationship between professional identity and job burnout is mediated by work engagement. The relationship between professional identity and job burnout is mediated by psychological capital. The relationship between professional identity and job burnout is sequentially mediated by work engagement and psychological capital.